SYSTEMATIC LITERATUR REVIEW: MEDIA PENANAMAN KARAKTER GEMAR MEMBACA BAGI SISWA SD - rani setiawaty; Nasywa Sabilarrahmah; Aat Alivia Nur Yasin; Vina Lailatul Oktaviani; Nila Amalia Nabila (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2025)
Reading is a very important skill to support children's academic success and character development. However, interest in reading among elementary school students in Indonesia is still relatively low. This research aims to explain the media used to instill the character of a love of reading. The method used is Systemtic Literature Review (SLR) by analyzing 21 related journals. Data was collected through the Google Scholar Database with the keywords